Empire and honor - Griffin, W. E. B.; Butterworth, William E. (New York : G. P. Putnam's Sons, 2012)
In the aftermath of the surrenders of Germany and Japan in October 1945, Cletus Frade and his colleagues in the OSS are given the life-threatening task of maintaining security during a covert U.S. deal with Germany for intelligence about the identities of Soviet spies in the American atomic bomb program.
Keywords: United States. -- Office of Strategic Services; Intelligence officers -- United States; World War, 1939-1945 -- Secret service -- United States; World War, 1939-1945 -- Secret service -- Soviet Union; Atomic bomb; World War, 1939-1945; Spy stories; Suspense fiction; Historical fiction